THE REGULATION. THE DECISION. THE DIRECTIVE. LEGISLATIVE DIFFFERENCES - GABRIEL ANDRONACHE (Challenges of the Knowledge Society)
The article is set to establish the elements that determined the European legislator, within the Lisbon Treaty, to conclude that for certain regulatory domains a specific type of legislative act is to be used (regulation, directive or decision), as well as to define the juridical dissimilarities between the 3 types of secondary legal acts.